MRI-guided coupling for a focused ultrasound system using a top-to-bottom propagation - Yiannakou, Marinos; Menikou, Georgios; Yiallouras, Christos; Damianou, Christakis A. (My University, 2017)
Background: A novel magnetic resonance imaging (MRI)-conditional coupling system was developed that accommodates a focused ultrasound (FUS) transducer. With this coupling system, the transducer can access targets from top to bottom. The intended clinical application is treatment of fibroids using FUS with the patient placed in supine position. Methods: The coupling system was manufactured using a rapid prototyping device using acrylonitrile butadiene styrene (ABS) plastic. Coupling to a gel phantom was achieved using a water bag filled with degassed water. The FUS transducer was immersed in the water bag. Results: The coupling system was successfully tested for MRI compatibility using fast-gradient pulse sequences in a gel phantom. The robotic system with its new coupling system was evaluated for its functionality for creating discrete and multiple (overlapping) lesions in the gel phantom. Conclusions: An MRI-conditional FUS coupling system integrated with an existing robotic system was developed that has the potential to create thermal lesions in targets using a top-to-bottom approach. This system has the potential to treat fibroid tumors with the patient lying in supine position.
Keywords: Cancer; Fibroid; MRI; Robot; Ultrasound